Understanding Pregnancy Diagnosis in Beef Cattle - G. Cliff Lamb; Darren D. Henry; Vitor R. G. Mercadante; Doug E. Mayo (EDIS)
Because 55 to 70 percent of the input costs associated with a beef cattle operation are related to nutrition, culling open (non-pregnant) cows after the breeding season can save as much as $200 per head that can be diverted to the purchase or development of replacement females, sire selection, increased nutritional management, and other management-related costs. Pregnancy diagnosis can be performed simply during vaccination or at the time of weaning. There are three practical methods: rectal palpation, transrectal ultrasonography, or blood test. This 5-page fact sheet was written by G. Cliff Lamb, Darren D. Henry, Vitor R. G. Mercadante, and Doug E. Mayo, and published by the UF Department of Animal Sciences, November 2014.